The Critical Study Of Valiantness In The Novel Mahashweta - Jyothi.Gedela; Dr. Manjiree Vaidya (Revista Electronica de Veterinaria, 2024)
This paper is studied from the perspective of a girl named Anupama who undergoes tremendous life changes after marriage when she comes across skin pigmentation because of leukoderma disease. Mahashweta is based on a Kannada novel through the literary work of Sudha Murty. Anupama the female protagonist is left behind by her husband after marriage and abandoned by her in-laws due to a white patch on her skin forced to leave home. The social stigma attached to such a disease forced her to leave contemporary society.